2012
DOI: 10.1016/j.jalz.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies to periodontal pathogens are a risk factor for Alzheimer's disease

Abstract: Background Chronic inflammation in periodontal disease has been suggested as a potential risk factor in Alzheimer’s disease. The purpose of this study was to examine serum antibody levels to bacteria of periodontal disease in participants who eventually converted to Alzheimer’s disease (AD) compared to the antibody levels in control subjects. Methods Serum from 158 participants in the BRAINS (Biologically Resilient Adults in Neurological Studies) research program at the University of Kentucky were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
327
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(346 citation statements)
references
References 58 publications
11
327
1
7
Order By: Relevance
“…This study supports the literature on elevated antibodies to periodontal diseaseassociated bacteria such as P. gingivalis, being found in AD patients (7). Furthermore, in 2,355 people 60 years and over, the third NHANES study found associations between periodontitis and cognitive impairment and between measures of immunoglobulin to P. gingivalis and cognitive test performance (96,97). In this study all participants were cognitively intact at baseline.…”
Section: Periodontal Bacterial Pathogens Are Related To Adsupporting
confidence: 88%
See 1 more Smart Citation
“…This study supports the literature on elevated antibodies to periodontal diseaseassociated bacteria such as P. gingivalis, being found in AD patients (7). Furthermore, in 2,355 people 60 years and over, the third NHANES study found associations between periodontitis and cognitive impairment and between measures of immunoglobulin to P. gingivalis and cognitive test performance (96,97). In this study all participants were cognitively intact at baseline.…”
Section: Periodontal Bacterial Pathogens Are Related To Adsupporting
confidence: 88%
“…In the NHANES study antibody levels to these organisms were significantly increased (α = 0.05) at baseline serum in patients with AD compared to controls (97). The results were significant after controlling for baseline age, Mini-Mental State Examination score, and allele APOEɛ4 status.…”
Section: Periodontal Bacterial Pathogens Are Related To Admentioning
confidence: 92%
“…When compared to the healthy individuals, people with AD had elevated plasma Ig G and TNF-α levels against periodontal bacteria (P. gingivalis, T. forsythia ve A. actinomycetemcomitans), There were no differences found in IL-1β and IL-6 levels (46). In a similar study, levels of F. nucleatum and P. intermedia antibodies seen in periodontal diseases were found to be elevated in people with AD compared to controls (47). The fact that periodontal diseases can be treated or managed suggested that they may pose a changeable risk factor for AD (48).…”
Section: Periodontal Statusmentioning
confidence: 86%
“…It was shown that periodontal treatment may lead to favorable systemic CRP levels (43,45). The possible relationships with Alzheimer's disease (AD), which is a neurodegenerative disease, and periodontal diseases, have also been investigated (46,47,48). When compared to the healthy individuals, people with AD had elevated plasma Ig G and TNF-α levels against periodontal bacteria (P. gingivalis, T. forsythia ve A. actinomycetemcomitans), There were no differences found in IL-1β and IL-6 levels (46).…”
Section: Periodontal Statusmentioning
confidence: 99%
“…(iii) the latest works report them as etiological agents in systemic infective-inflammatory or in autoimmune diseases such as rheumatoid arthritis and in atheromatous plaques [5][6][7], infective endocarditis and some researchers have recently suggested their role in neurogenerative diseases such as Alzheimer's disease [8], while it is certain that F. nucleatum is associated with intestinal cancer.…”
Section: Open Access Journal Of Surgerymentioning
confidence: 99%